Genus, design och marknad: En introduktion - Mörck, Magnus; Petersson, Magdalena (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2007)
This introductory contribution from the editors points to the possibilities of design to question taken for granted notions of gender. Starting from our own project Design, Gender and Organisation, which brings together a multidisciplinary team of ethnologists and also Marcus Jahnke, designer and Lena Hansson, doctor i marketing, we discuss the possibilities of integrating poststructuralism and contemporary conceptual design dealing with gender. The methods have included artistic research in a combination of theoretical work, fieldwork among designers and development of design prototypes that have been used to collect responses from various potential users. The problematic relation between ethnology, as well as feminism, with the market is further addressed and reformulated using new theorizing, without forgetting the misgivings voiced by Spivak.